2012
DOI: 10.1097/md.0b013e31826b145a
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implantation in Older Adults

Abstract: Cochlear implants allow individuals with severe-to-profound hearing loss access to sound and spoken language. The number of older adults in the United States who are potential candidates for cochlear implantation is approximately 150,000 and will continue to increase with the aging of the population. Should cochlear implantation (CI) be routinely recommended for these older adults, and do these individuals benefit from CI? We reviewed our 12 year experience with cochlear implantation in adults ≥60 years (n = 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
1
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 129 publications
(104 citation statements)
references
References 132 publications
5
94
1
4
Order By: Relevance
“…When outcomes of cochlear implantation in adults older than 60 years were analyzed, post-cochlear implantation hearing-in noise test (CI HINT) scores were significantly improved after the operation. Individuals with higher pre-CI HINT scores had significantly greater post-CI HINT score improvement (40-60%) than those with lower pre-CI HINT scores (<40% improvement) after adjusting for age at hearing loss onset (7). The same study also showed that the gain in speech scores was negatively affected as the time interval between the hearing loss onset and the timing of cochlear implantation.…”
Section: Discussionsupporting
confidence: 61%
“…When outcomes of cochlear implantation in adults older than 60 years were analyzed, post-cochlear implantation hearing-in noise test (CI HINT) scores were significantly improved after the operation. Individuals with higher pre-CI HINT scores had significantly greater post-CI HINT score improvement (40-60%) than those with lower pre-CI HINT scores (<40% improvement) after adjusting for age at hearing loss onset (7). The same study also showed that the gain in speech scores was negatively affected as the time interval between the hearing loss onset and the timing of cochlear implantation.…”
Section: Discussionsupporting
confidence: 61%
“…The high rates of long-term CI use in older adults are consistent with the findings from previous studies demonstrating improved speech perception abilities and better health-related quality of life after CI in this population. 15,[19][20][21] We found that earlier age at implantation was associated with a greater rate of regular CI use. These results are consistent with earlier data from our research group demonstrating that earlier intervention was also associated with greater speech perception scores after CI in older adults.…”
Section: Discussionmentioning
confidence: 64%
“…Individuals with higher pre-CI speech scores had significantly greater post-CI than those with lower pre-CI speech scores after adjusting for age at CI and age at hearing loss onset. In the future, research of CI in older patients should expand its evaluations to take into account the broad cognitive, social and physical outcomes that are likely detrimentally impacted by hearing loss [14].…”
Section: Resultsmentioning
confidence: 99%